Geographic Variation of Diapause Induction and Termination in the Spider Mite Tetrαnychus urticαe: Α mini-review - Koveos, D. S.; Veerman, A. (ENTOMOLOGIA HELLENICA, 1998)
In eight strains of the spider mite Tetranychus urticae Koch (Acari: Tetranychidae), originating from different localities in Europe, the critical daylength for diapause induction and termination was almost the same in each strain but varied with the latitudinal origin of the strains; critical daylength was shorter in strains originating from lower latitudes and longer in those from higher latitudes. Diapause intensity, measured as the period of chilling required for diapause termination under a short day photoperiod (LD 10:14) and 19°C, again varied with the latitudinal origin of each strain, being higher the more northern the origin of the strain. An exception were two mountain strains which showed a longer critical daylength and a deeper diapause than expected on the basis of their latitudinal origin. The number of long-day (LD 17:7) cycles required for 50% diapause termination after a certain period of chilling was higher in the northern and lower in the southern strains. These results indicate that geographic strains of T urticae may differ considerably in their diapause attributes, which may be explained as an adaptation to local climatic conditions. The great plasticity of the diapause response may, among other factors, have been responsible for the wide distribution of this mite species.